2009
DOI: 10.1164/rccm.200812-1929oc
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Physical Activity and Risk of Asthma Exacerbations in Older Women

Abstract: Rationale: The potential role of physical activity in preventing asthma exacerbations is unknown. Objectives: To investigate the longitudinal association between regular physical activity and asthma exacerbations. Methods: A total of 2,818 women with asthma from a large U.S. cohort (the Nurses' Health Study) were monitored from 1998 to 2000. Physical activity was self-reported at baseline, using a validated questionnaire, and categorized in quintiles. Exacerbations during follow-up were defined as a self-repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(69 citation statements)
references
References 27 publications
(37 reference statements)
3
58
0
8
Order By: Relevance
“…Interestingly, a recent study showed that asthmatic females with higher physical fitness present with less episodes of asthma exacerbations. The authors hypothesised that an increase in physical fitness should be used as adjuvant treatment in asthma [40], which is supported by our findings.…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, a recent study showed that asthmatic females with higher physical fitness present with less episodes of asthma exacerbations. The authors hypothesised that an increase in physical fitness should be used as adjuvant treatment in asthma [40], which is supported by our findings.…”
Section: Discussionsupporting
confidence: 87%
“…Oral corticosteroid used continuously may also be considered as a marker of asthma severity. In previous studies, exacerbations were defined only by hospitalisation or emergency aspects [31], or in addition to the ''use of oral corticosteroids when needed'' to evaluate severe exacerbations [21]. In ECRHS both aspects of exacerbations seem to be linked to occupational exposure to asthmagens [21].…”
Section: Figurementioning
confidence: 99%
“…These epidemiological data suggest that increased prevalence of asthma could be a consequence of changes in lifestyle related to physical activity and dietary habits, as confirmed by the increased prevalence of obesity worldwide, also at young age. In addition, a large longitudinal study recently found a decreased risk of asthma exacerbations associated with regular physical activity in older women (Garcia-Aymerich et al, 2009), suggesting that exercise may positively affect asthma control.…”
Section: Do Acute Exercise and Training Decrease Bronchial Reactivity?mentioning
confidence: 99%